2023
DOI: 10.3390/epigenomes7020010
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase Modulation: Epigenetic Strategy to Combat Cancer Progression

Abstract: Epigenetic modifications are heritable, reversible changes in histones or the DNA that control gene functions, being exogenous to the genomic sequence itself. Human diseases, particularly cancer, are frequently connected to epigenetic dysregulations. One of them is histone methylation, which is a dynamically reversible and synchronously regulated process that orchestrates the three-dimensional epigenome, nuclear processes of transcription, DNA repair, cell cycle, and epigenetic functions, by adding or removing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 177 publications
(246 reference statements)
0
1
0
Order By: Relevance
“…Lysine demethylase 5C (KDM5C), alternatively referred to as JARID1C or SMCX, serves as a demethylase specifically targeting H3K4me2/3 in mammalian cells 179 . KDM5C is widely acknowledged as a tumor suppressor due to its role in modulating enhancer activities across multiple cancer types, including prostate, breast, cervix, and clear-cell renal carcinoma 180 . Despite some RNA interference (RNAi) experiments, which indicated that KDM5C defects exhibited anticancer effects, the efficacies of several reported KDM5C inhibitors for exerting potent anticancer effects remain limited 181 .…”
Section: Histone Methylation-/demethylation-related Targetsmentioning
confidence: 99%
“…Lysine demethylase 5C (KDM5C), alternatively referred to as JARID1C or SMCX, serves as a demethylase specifically targeting H3K4me2/3 in mammalian cells 179 . KDM5C is widely acknowledged as a tumor suppressor due to its role in modulating enhancer activities across multiple cancer types, including prostate, breast, cervix, and clear-cell renal carcinoma 180 . Despite some RNA interference (RNAi) experiments, which indicated that KDM5C defects exhibited anticancer effects, the efficacies of several reported KDM5C inhibitors for exerting potent anticancer effects remain limited 181 .…”
Section: Histone Methylation-/demethylation-related Targetsmentioning
confidence: 99%